Structural and Aeroelastic Studies of Wing Model with Metal Additive Manufacturing for Transonic Wind Tunnel Test by NACA 0008 Example - Natsuki Tsushima; Kenichi Saitoh; Hitoshi Arizono; Kazuyuki Nakakita (Aerospace, 2021)
Additive manufacturing (AM) technology has a potential to improve manufacturing costs and may help to achieve high-performance aerospace structures. One of the application candidates would be a wind tunnel wing model. A wing tunnel model requires sophisticated designs and precise fabrications for accurate experiments, which frequently increase manufacturing costs. A flutter wind tunnel testing, especially, requires a significant cost due to strict requirements in terms of structural and aeroelastic characteristics avoiding structural failures and producing a flutter within the wind tunnel test environment. The additive manufacturing technique may help to reduce the expensive testing cost and allows investigation of aeroelastic characteristics of new designs in aerospace structures as needed. In this paper, a metal wing model made with the additive manufacturing technique for a transonic flutter test is studied. Structural/aeroelastic characteristics of an additively manufactured wing model are evaluated numerically and experimentally. The transonic wind tunnel experiment demonstrated the feasibility of the metal AM-based wings in a transonic flutter wind tunnel testing showing the capability to provide reliable experimental data, which was consistent with numerical solutions.